Dyspnea as Manifestation of a Rare Disease - Margarida Pedro Antunes Ferreira Gaudêncio, Ana; Antunes, Joana; Barreiro, Ivo; Bertão, Maria Inês; Bessa, Maria Isabel; Pereira, Maria Amélia (Gazeta Médica, 2021)
Madelung’s disease is a rare condition characterized by a symmetrical and painless pattern of massive fatty deposits. The condition is also known as benign or multiple symmetric lipomatosis. Two types of this disease have been described. In type 1, fat accumulates around the neck, shoulders, upper arms and upper back. In type 2, lipomas are distributed over much of the body, including the hips and thighs. The patients complain of their appearance although, in advanced cases, the increase in lipomas could cause symptoms as dyspnea or dysphagia. The authors propose to present the clinical case of a 70-year-old male patient referred to the emergency department for dyspnea with a few months of evolution, with worsening in the last 6 days, associated with cough. At physical examination, had no changes, except the presence of lipomas at the cervical and upper thoracic and back levels, with symmetrical distribution and collateral venous circulation. Computed tomography (CT) angiography of neck and thorax have shown proliferation of cervical fat suggestive of Madelung’s disease, with compression of the jugular veins and right brachiocephalic vein, as well as formation of collateral veins and a peribronchial consolidation in the lower and middle lobes with air bronchogram. He was hospitalized for oxygen and empirically antibiotic therapy. He had a good clinical and analytical evolution and was discharged after 5 days of hospitalization, oriented to Surgery’s consultation. The case presented corresponds to a Madelung’s disease type 1, in which deep involvement conditioned the onset of dyspnea exacerbated by infectious intercurrence. The diagnosis of Madelung’s disease is primarily based on clinical history, physical examination and imaging studies. The clinical diagnosis is based on the recognition of the unique appearance of the patient. The etiology of this disease remains unknown. Currently, surgery is the only treatment available, despite the high recurrence rate.